2009
DOI: 10.1007/s11089-009-0239-1
|View full text |Cite
|
Sign up to set email alerts
|

Religious Resources, Spiritual Struggles, and Mental Health in a Nationwide Sample of PCUSA Clergy

Abstract: A growing body of research explores patterns and correlates of mental health among clergy and other religious professionals. Our study augments this work by distinguishing between religious resources (i.e., support from church members, positive religious coping practices), and spiritual struggles (i.e., troubled relations with God, negative interactions with members, chronic religious doubts). We also explore several conceptual models of the interplay between these positive and negative religious domains and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 67 publications
0
39
0
Order By: Relevance
“…Specifically, there was concern about losing one's job or not getting promoted, both of which have been demonstrated in previous studies (Ellison et al, 2010). However, participants were also concerned about being seen as unable to cope, in particular mental health professionals described wanting to put on a brave face and not let the team down.…”
Section: Discussionmentioning
confidence: 84%
“…Specifically, there was concern about losing one's job or not getting promoted, both of which have been demonstrated in previous studies (Ellison et al, 2010). However, participants were also concerned about being seen as unable to cope, in particular mental health professionals described wanting to put on a brave face and not let the team down.…”
Section: Discussionmentioning
confidence: 84%
“…Studies have examined the potential for these negative religious responses in a wide variety of samples, including, for example, college-aged adults (Bryant & Astin, 2008), Presbyterian ministers (Ellison, Roalson, Guillory, Flannelly, & Marcum, 2010), Jews (Rosmarin, Pargament, & Flannelly, 2009), individuals recently experiencing a serious illness or injury (McConnell, Pargament, Ellison, & Flannelly, 2006), caregivers of people with Alzheimer's disease (Shah, Snow, & Kunik, 2001), terminally ill medical patients (Edmondson, Park, Chaudoir, & Wortmann, 2008), victims of the 1993 flooding in the Midwest (Smith, Pargament, Brant, & Oliver, 2000), and church members living in proximity to the Oklahoma City bombing (Pargament, Smith, Koenig, & Perez, 1998). This research has repeatedly demonstrated associations between struggling with one's faith and poorer physical and psychological functioning (Exline & Martin, 2005;Pargament, 2002;Pargament, Murray-Swank, Magyar, & Ano, 2005).…”
Section: Negative Religious Responses and Health Outcomesmentioning
confidence: 99%
“…This study was conducted by Ellison and his colleagues [7]. These investigators were unable to find support for the notion that negative aspects of religion (i.e., spiritual struggles and religious doubt) exacerbate the effects of stress on psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
“…However, researchers have known for some time that there are negative as well as positive aspects of religion. For example, there is some evidence that negative interaction with fellow church members [7], as well as religious doubt [8], may have a noxious effect on health and well-being. If the positive aspects of religious life reduce the pernicious effects of stress on health and well-being, then it follows that the negative dimensions of religion may have the opposite effect: Instead of helping people cope more effectively with stress, the so-called “dark side” of religion may actually exacerbate the effects of stress on well-being [9].…”
Section: Introductionmentioning
confidence: 99%